Application of the chloridizing roasting method for the removal of copper and sulphur from copper slags. Issue 1 (2nd January 2018) - Li, Lei; Hu, Jian-hang; Wang, Hua
ABSTRACT: A chloridizing roasting process was used to remove copper and sulphur from copper slags in this study. Higher holding temperature and longer residence time were beneficial to the removal of copper and sulphur. Massive 2CaO·SiO2 was produced with O2 velocity and CaCl2 addition amount being increased over a proper value, enclosing the unreacted CaCl2 particles and reducing the decoppering rate. Sulphur was removed effectively through the action of chlorination and direct oxidization. 2FeO·SiO2 was oxidized to Fe3 O4 and Fe2 O3 in this process, and the chlorination of these two species was difficult to implement, causing low iron losses of approximately 5%. The resulting decoppering rate of 92.21% and slag sulphur content of 0.0363% were obtained at the optimum conditions of holding temperature of 1473 K, residence time of 60 min, CaCl2 addition amount of 0.14 (mass ratio of CaCl2 to the copper slag) and oxygen flow rate of 0.3 L min −1 .